Nanocomposites of medicobiologic destination: reality and perspectives for oncology. Review - Gorbyk, P.P.; Chekhun, V.F. (Functional Materials, 2012)
Analysis is given of the ways of creation of polyfunctional medicobiologic nanocomposites with multilevel hierarchic architecture that would be applicable for recognition of microbiological objects in biologic media, targeted delivery and deposition of drugs in target organs, diagnostics and therapy of diseases on the cellular level. The physicochemical experimental data, as well as medicobiological studies, confirm their perspective for preparation of new medicinal forms with complex (cytotoxic, immunotherapeutic and hyperthermic) activity.